2022
DOI: 10.3390/biology11111644
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Single and Multi-Strain Probiotics on In Vitro Strain Compatibility, Pathogen Inhibition, Biofilm Formation Capability, and Stress Tolerance

Abstract: Compatibility of each strain in a multi-strain probiotic (MSP), along with its properties, becomes a strong base for its formulation. In this study, single-strain probiotics (SSPs) and multi-strain probiotics (MSPs) were evaluated in vitro for strain compatibility, microbial antagonism, biofilm formation capacity, and stress tolerance. Bacillus amyloliquefaciens L11, Enterococcus hirae LAB3, and Lysinibacillus fusiformis SPS11 were chosen as MSP1 candidates because they showed much stronger antagonism to Aerom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Probiotics containing multiple groups of bacteria with different mechanisms of action tend to have synergistic effects on each other and have a broad spectrum of activity [252,254]. For insistence, the MSP of Bacillus amyloliquefacrem, Enterococcus hirae, and Lysinibacillus fusiformis was able to significantly inhibit the growth and biofilm formation of Aeromonas hydrophila compared to the individual probiotics [255]. Multi-species probiotics (L. reuteri, E. faecium, B. animalis, P. acidilactici, and L. salivarius) greatly reduce S. Enteritidis infections (up to 2.7 log reduction) in poultry [256].…”
Section: Antibiotics Used For Salmonella Treatment and Antimicrobial ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics containing multiple groups of bacteria with different mechanisms of action tend to have synergistic effects on each other and have a broad spectrum of activity [252,254]. For insistence, the MSP of Bacillus amyloliquefacrem, Enterococcus hirae, and Lysinibacillus fusiformis was able to significantly inhibit the growth and biofilm formation of Aeromonas hydrophila compared to the individual probiotics [255]. Multi-species probiotics (L. reuteri, E. faecium, B. animalis, P. acidilactici, and L. salivarius) greatly reduce S. Enteritidis infections (up to 2.7 log reduction) in poultry [256].…”
Section: Antibiotics Used For Salmonella Treatment and Antimicrobial ...mentioning
confidence: 99%
“…Probiotics are classified as mono-strain or single-strain probiotics (SSP), multi-strain probiotics (MSP), and multi-species probiotics [253,254]. Singlestrain probiotics (SSP) can provide limited health benefits to the host [255]. Probiotics containing multiple groups of bacteria with different mechanisms of action tend to have synergistic effects on each other and have a broad spectrum of activity [254,256].…”
Section: Probioticsmentioning
confidence: 99%
“… 14–16 The potential impact of multi-strain probiotic formulas, as opposed to single-strain probiotics, on the host is greater because the strains within the formula can complement each other. 17 Previous studies have shown that the oral administration of a probiotic formula, Ecologic® 825, to healthy volunteers did not result in an overall shift in fecal community composition of the microbiota. However, the LEfSe analyses identified two features belonging to a Bacteroides sp.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, probiotics are used in prevention and treatment of several disorders [13, 14]. It has been widely accepted that the impact of multi strain probiotic formulas instead of single strain probiotics is potentially greater on the host since the strains within the formula can complement each other [15]. Indeed, oral administration of a probiotic formula (Ecologic® 825) to healthy volunteers resulted in a minor shift in the fecal microbiota [16], while when administered orally to patients with irritable bowel syndrome, an increase in fecal levels of acetate and butyrate, accompanied by a reduction in fecal zonulin and symptom severity were observed [17].…”
Section: Introductionmentioning
confidence: 99%